Determinasi Keputusan Penggunaan BSB Mobile: Peran Fitur Layanan, Desain User Interface, dan Keamanan Digital (Studi Kasus Bank Sumsel Babel Cabang Syariah Palembang) - M. Diva Faundra (CV. Era Digital Nusantara, 2025)
The purpose of this study is to determine the extent of the influence of Service Features, User Interface Design, and Digital Security on customers' decisions to use BSB Mobile at Bank Sumsel Babel Syariah Branch Palembang. This research uses a quantitative approach, with data collection through a questionnaire using a Likert scale for assessment. The population of this study consists of customers of Bank Sumsel Babel Syariah Branch Palembang who use BSB Mobile. A sample of 100 respondents was selected using purposive sampling, and the sample size was determined using the Slovin formula. Data analysis was conducted using multiple linear regression with SPSS version 26. Based on hypothesis testing, the results show that Service Features have a positive and significant effect on customers' decisions to use BSB Mobile, as indicated by the t-value of 2.472, where the t-value is greater than the t-table value of 1.984 and the sig value is 0.015 < 0.05. User Interface Design also has a positive and significant effect on customer decisions, with a t-value of 3.715, where the t-value is greater than the t-table value of 1.984 and the sig value is 0.000 < 0.05. Digital Security also has a positive and significant effect on customer decisions, with a t-value of 3.467, where the t-value is greater than the t-table value of 1.984 and the sig value is 0.001 < 0.05.